Linear Analysis for Performance of Dual Mass Flywheel with Centrifugal Pendulum Vibration Absorbers System - Guangming Zhao; Zhengfeng Jiang; Lei Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this study we have offered an investigation of DMF-CPVAs setup for isolating torsional vibration from engine. The simplified mathematical model of DMF-CPVAs setup is built based on the linear theory, the performance of the setup is analyzed, and the result shows that using CPVAs on the DMF leads to an advantage of isolation vibration, instead of just damping vibrations at a specific frequency, could dampen vibrations over a range of frequencies. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2462